Upgrading Of Clay Deposit By Selective Grinding And Air Classification For Use In Portland Cement Manufacture (4ed84707-3e27-4e99-aef2-c309071cc1e5) - Sidney M. Cohen (Society for Mining, Metallurgy & Exploration, 1983)
[Portland cement is a product made from a combination of limestone and argillaceous material which would supply the necessary amounts f calcium, silica, alumina and iron to form cementious compounds when fired at high temperatures. The resulting mixture, usually around 80% limestone and 20% argillaceous, is ground nine (80% -200 mesh), blended and then fired1 (2600-2700°F) to produce a cement clinker from which the final cement product is produced by grinding. The argillaceous component can be shale, clay, slate or other sources of the individual components of silica, alumina and iron. This paper deals with a case where a clay component was under consideration. The planned Plant site was to be located at a well defined limestone deposit. When it came to the argillaceous component, the nearest uniform deposit of clay was over 50 miles away and would require purchase of land or clay from the owner plus the daily delivery costs to the plant site. This situation made the plant site economically questionable. It was decided that a local clay deposit, which was available at the plant site but was orginally not considered due to lack of chemical uniformity and its high free silica content, would be reconsidered.]